Influência da natureza do contra corpo, da distribuição do tamanho das partículas abrasivas e da velocidade no ensaio de microabrasão - Esteves, Pâmella Jureves (2018)
Micro-abrasion tests were carried out to analyze the influence of two parameters on the wear coefficient: the abrasive particle size distribution using different counter bodies and the ball rotation speed. To obtain different size distributions, two abrasive powders having an average particle size of 5.97 μm (0 G) and 14.39 μm (100 G) were mixed. The tests were conducted using AISI 1020 steel samples and balls made of AISI 52100 martensitic steel, AISI 304 austenitic stainless steel, polyurethane rubber and zirconia-alumina. The change in ball material resulted in different behaviors of the wear coefficient with the variation of particle size. When using the AISI 52100 martensitic steel ball, the lowest wear coefficients were mainly obtained with the mixture with 50%, in mass, of the powder with the largest average particle diameter, a result that has already been reported by Gomez et al. (2015). When using the AISI 304 austenitic stainless steel ball, the lowest wear coefficients were obtained with the mixture with 20%, in mass, of the powder with the largest average particle diameter. The use of a highly elastic polyurethane rubber ball resulted in no changes in the wear coefficient with the different grain sizes. On the other hand, with zirconia-alumina balls, a linear relationship between the wear coefficient and the increase of the mass fraction of the powder with the largest abrasive particle size was observed. For the study of ball rotation speed, tests were conducted with 40, 80 and 150 rpm, using AISI 1020 steel samples and AISI 52100 martensitic steel balls. In addition, the abrasive slurry was prepared with silicon carbide (SiC) particles with average sizes of 2.11 μm (A) or 6.57 μm (B), with a fixed abrasive concentration (0.1 g/cm³) or with a concentration that decreased as a function of the rotation speed, to maintain constant the amount of abrasive during one single test. A general trend of decrease in wear coefficient with the increase in speed was observed. Scanning Electron Microscopy (SEM) analyses allowed observing that tests with different particle size distributions resulted, mainly, in grooving abrasion with microlling, except for rubber, wich resulted only in grooving abrasion. In the tests varying the rotation speed, the micro mechanism was grooving abrasion with microlling